Perceived Benefits of Future Teachers on the Usefulness of Virtual and Augmented Reality in the Teaching-Learning Process - Raimundo Castaño-Calle; Amparo Jiménez-Vivas; Raquel Poy Castro; María Isabel Calvo Álvarez; Cristina Jenaro (Education Sciences, 2022)
Virtual and augmented reality technologies are increasingly being implemented in education and there is a growing body of evidence on their usefulness for training academic and non-academic skills among student with different education levels and diverse educational needs. To fully benefit from their use, teachers need to know the different existing tools and their potential, as well as be trained and motivated in their use. The current study aims to evaluate the factors that promote and hinder the use of virtual and augmented reality in future teaching professionals. Data were gathered by means of an online questionnaire from a total of 422 Spanish students from the Universidad Pontificia de Salamanca (Spain). Instrumental analyses (Cronbach’s Alpha, and CFA) were performed, together with descriptive, correlational, and inferential tests (Manova, Anova, and Student’s T test) to contrast the hypotheses. Results indicate that participants show favorable attitudes towards these technologies, but have little knowledge of them. Age, year of study, and knowledge are associated with a higher perception of usefulness as tools for teaching and learning and for promoting inclusion. The results support the relevance of providing knowledge, and enhancing skills, thus fostering positive attitudes towards these technologies.